In-Hospital Cost Comparison for Open Versus Endoscopic Endonasal Approach for Meningioma Resection. Issue 3 (May 2023) - Parasher, Arjun K.; Lerner, David K.; Miranda, Stephen P.; Douglas, Jennifer E.; Glicksman, Jordan T.; Alexander, Tyler; Lin, Theodore; Ebesutani, Darren; Kohanski, Michael; Lee, John Y.K.; Storm, Phillip B.; O'Malley, Bert W.; et al.
Objective: To determine the in-hospital cost implications of an endoscopic expanded endonasal approach (EEEA) for meningioma resection relative to the open transcranial approach. Methods: All anterior skull base meningioma surgeries performed over a period from January 1 st, 2015 to October 31th, 2017 were evaluated. The electronic medical record was reviewed for patient factors, tumor characteristics, and cost variables associated with each hospital stay and univariate analysis was performed using R software. All cost data were converted into August 2021-equivalent dollar amounts using the United States Bureau of Labor Statistics consumer price index. Results: Thirty-five patients met study criteria, including 27 patients undergoing an open transcranial approach and 8 undergoing an EEEA. Average length of stay for patients undergoing an open approach was 9.3 days compared to 5.6 within the EEEA group ( P  = .126). The average total in-hospital cost of patient undergoing an EEEA was $35417.1 compared to $46406.9 among patients undergoing an open transcranial approach ( P  = .168). On univariate analysis, the cost of an open transcranial approach relative to the EEEA was $10989.8 ( P  = .411). Conclusions: The open transcranial approach remained the dominant surgical approach to anterior skull base meningiomas over our study time period. However, despite limited patient numbers the EEEA was associated with decreased total in-hospital costs.